Effect of Sonication Power on Al2O3 Coated LiNi0.5Mn0.3Co0.2O2 Cathode Material for LIB - Dila Sivlin; Ozgul Keles (The Minerals, Metals and Materials Society, 2018)
Lithium ion batteries are potential energy source of next generation electric vehicles (EVs). However, some problems such as safety, durability, low capacity, cycle life etc. restrict their use in EVs. These problems mostly related with cathode materials, an improvement in cathode materials may cause significant changes in battery performance. In this work, to overcome cycle life problem Al2O3 coating on LiNi0.5Mn0.3Co0.2O2 cathode material produced by sol-gel method. The surface modification of LiNi0.5Mn0.3Co0,2O2 was started by adding LiNi0.5Mn0.3Co0.2O2 powders into alumina sol. Then, sonication was started and two different sonication powers were tested (45, 100%). After the second gel is obtained, last heat treatment for Al2O3 crystallization was done at 600 °C for 4 h. X-ray diffraction (XRD) measurements showed that the material had a well-ordered layered structure and Al was not in the LiNi0.5Mn0.3Co0.2O2. Al2O3 coated materials show better cycling performance compared to the pristine material. It is believed that, this improvement is caused by the fact that Al2O3 layer prevents direct contact between active material and electrolyte and reducing decomposition reactions.